Reduced parasite diversity and abundance in a marine whelk in its expanded geographical range. (5th May 2014) - Hopper, Julie V.; Kuris, Armand M.; Lorda, Julio; Simmonds, Sara E.; White, Crow; Hechinger, Ryan F.; Veech, Joseph
Abstract Aim To improve our understanding of how parasitism interacts with geographical range expansions by quantifying diversity and abundance of parasites in 25 populations of a large marine snail, Kellet's whelk (Kelletia kelletii), throughout its historical and recently expanded range, which are separated by a well‐known biogeographical boundary. Location California coast (western North America). Methods Parasitological examinations were conducted on 199 whelks from 25 subtidal reefs throughout its expanded and historical ranges. We calculated infection risk, parasite intensity, and parasite species diversity. Abiotic (temperature, latitude, distance from range limit) and biotic (host density) variables were analysed as potential drivers of differential parasitism between expanded‐ and historical‐range populations. Results Compared with historical‐range whelks, expanded‐range whelks were 20% as likely to be infected by parasites, and those that were infected had 6% the number of individual parasites. On average, expanded‐range whelks had 14% the number of parasite species than the historical‐range whelks. The marked decrease in species richness of parasites infecting expanded‐range whelks was only partly explained by the low numbers of parasites. The reduced parasite abundance and diversity in the expanded‐range whelks was not explained by the examined abiotic factors or by whelk density. Main conclusions Expanded‐range populations of Kellet's whelk experience substantially lower parasite abundance and diversity than the historical‐range populations, despite relatively poor demographic performance. The reduced parasitism observed resembles the enemy escape typically characterizing invasive species. A possible explanation for the observed 'parasite escape' is that the biogeographical boundary limits the movements or drives the low abundance of other host species (elasmobranchs) required to complete the life cycles of the 'missing' parasites. We suggest that parasite escape may generally characterize range‐margin expansions and be important in permitting expansions into what may otherwise be marginal habitats. This parasite escape may directly counter the spread of infectious diseases associated with global warming‐induced range shifts.